Addition of EGCG to self-etching primer: effect on adhesive properties and bond stability to dentin - Fernandes, Fernando Pelegrim (2020)
This study evaluated how adding EGCG to a SEP (Clearfil SE Bond, Kuraray) affects the physicomechanical properties of adhesive, and the long-term microtensile bond strength (µTBS) to dentin. Flexural strength (FS, n = 10) and degree of conversion (DC, n = 5) of the adhesive were analyzed after adding EGCG to SEP in two forms (powder or diluted in water), and in different concentrations (0.00%–control, 0.01%, 0.02% and 0.05%). The µTBS was tested by randomly dividing dentin fragments into 4 groups (n = 10): EGCG-SEP: EGCG (0.01%) added to SEP; EGCG-PRE: EGCG (0.01%) dentin pretreatment; CHX-PRE: 2% chlorhexidine dentin pretreatment; SEP: SEP applied without modification. After restoration of the dentin surface, beam-shaped specimens were submitted to µTBS after 24 h or 12 months of storage in artificial saliva. Particle size (PS), polydispersity index (PDI) and zeta potential (ZP) of EGCG-SEP and SEP solutions were measured at different storage periods (baseline, 14 or 28 days). Data was submitted to ANOVA or Kruskal–Wallis tests (α = 0.05). FS (p = 0.485) and DC (p = 0.6067) were not different among the groups. CHX-PRE and EGCG-PRE had significantly higher µTBS means than EGCG-SEP, but none differed from SEP (p = 0.053). µTBS decreased significantly after 12 months of storage (p < 0.001). PS (p < 0.001), and ZP (p = 0.003) means in EGCG-SEP were statistically higher and more negative, respectively, than SEP. PDI did not differ among the groups (p > 0.05). Incorporation of EGCG into SEP did not change adhesive properties; however, it influenced solution stability and did not prevent the decrease in long-term µTBS to dentin.